Clinical features and dosimetric evaluation of carbon ion radiation-induced osteoradionecrosis of mandible in head and neck tumors. (August 2021) - Musha, Atsushi; Shimada, Hirofumi; Kubo, Nobuteru; Kawamura, Hidemasa; Okano, Naoko; Sato, Hiro; Kaminuma, Takuya; Okada, Kohei; Anakura, Mai; Adachi, Akiko; Shirai, Katsuyuki; Saitoh, Jun-ichi; et al.
Highlights: Osteoradionecrosis (ORN) affects patient's quality of life. This study analyzed carbon-ion radiotherapy-induced ORN of the mandible. The volume of mandible and teeth receiving 30 Gy(RBE) was the most significant. Our study will help define clinical strategies for C-ion RT of the head and neck. Abstract: Background and purpose: Osteoradionecrosis (ORN) affects the patient's quality of life by making eating and maintaining oral hygiene painful. This study aimed to analyze carbon ion radiotherapy (C-ion RT)-induced ORN of the mandible. Materials and methods: A retrospective study of 199 patients with head and neck tumors treated with C-ion RT was performed from 2010 to 2019. Only 11 patients with tumors located in the oropharynx and floor of the mouth were analyzed. C-ion RT consisted of 57.6 Gy or 64.0 Gy (relative biological effectiveness) in 16 fractions. The mandible was analyzed for magnetic resonance imaging (MRI) changes and bone exposure. The relationship between the radiation dose and ORN of the mandible was analyzed. Results: Five patients (45.5%) had ORN of the mandible. The median follow-up time was 68 months. The median onset times based on MRI changes and bone exposure were 9 and 15 months, respectively. Doses of 30 Gy (relative biological effectiveness) to the mandible and teeth showed the most significant effect, causing ORN at 29.5 ± 6.7 cc and 3.9 ± 1.8 cc, respectively, with cut-off values at 16.5 cc ( p  = 0.002) and 1.8 cc ( p  = 0.0059), respectively. Conclusion: This is the first study reporting the incidence, onset time, and risk-predictive dosimetry parameters of C-ion RT-induced ORN of the mandible. Our study will be useful for establishing clinical strategies for C-ion RT to the head and neck near the mandible.